Easy Access, Sense of Security: The Foundation of Tourist Satisfaction in Bali's Coastal Areas - Andika, Ary Wira; Bunyamin, Ilham Akbar; Muhtadi, Muhamad Ammar (Westscience Press, 2025)
This study investigates the influence of easy access and sense of security on tourist satisfaction in the Bali coastal area. A quantitative approach was employed, involving 350 domestic and international tourists who responded to a structured questionnaire using a 5-point Likert scale. Data were analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS 3). The results indicate that both easy access and sense of security significantly and positively impact tourist satisfaction. The coefficient of determination shows that these two variables explain of the variance in satisfaction. The model also demonstrated good reliability and predictive relevance. These findings suggest that enhancing accessibility infrastructure and ensuring visitor safety are key strategies for increasing satisfaction and encouraging return visits. Bali's tourism stakeholders should prioritize both transportation convenience and comprehensive safety measures to maintain competitiveness in the global tourism market.